Solutions to problems in differential calculus SI : Metric Edition - Arreola, Matias (Quezon City, Philippines : Ken Inc., 1995)
In 1960 the Paris based international bureau of weights and measures proposed a system of units to be used by all countries for commerce, industry and science, named Systeme Internationale d' Unites of S.I.
Chapter 1. Variables and functions -- Chapter 2. Limits and continuity -- Chapter 3. The derivative -- Chapter 4. Maxima and Minima -- Chapter 5. Practical applications of maxima and minima -- Chapter 6. Time rates -- Chapter 7. The differential -- Chapter 8. Solution of equations: Newton's Method -- Chapter 9. Indeterminate forms -- Chapter 10. Geometric applications of the derivative -- Chapter 11. Curvature: Radius and circle of curvature -- Chapter 12. Curve tracing.
Keywords: CALCULUS -- SI